Variations in performance-degradation behavior of Pt/CNF and Pt/C MEAs for the same degree of carbon corrosion - Park, Jae Hyun; Hwang, Sun Mi; Park, Gu Gon; Park, Seok Hee; Park, Eun Duck; Yim, Sung Dae (Electrochimica Acta, 2018)
Carbon corrosion due to high voltages encountered during the operation of fuel cells and the accompanying deterioration of cell performance are among the main issues affecting the durability of fuel cells. In this study, the carbon-corrosion durability of membrane electrode assemblies (MEAs) fabricated with Pt/CNF and Pt/C catalysts is studied using an accelerated stress test (AST) while applying high potentials. We compare the cell performance for the same degree of carbon corrosion, and the two MEAs show almost the same degradation behavior at the early stage of carbon corrosion. However, as the degree of carbon corrosion is increased, the performance-decay behavior of the two MEAs differs significantly, with there being a more serious performance decay in Pt/C than Pt/CNF, even at the same degree of carbon corrosion. The different behavior of the performance degradation between the two MEAs is due to the different catalyst layer structure, which results from the different catalyst-support morphologies between the three-dimensional (3D) high-structure Vulcan carbon (VC) and the one-dimensional (1D) structure of platelet carbon nanofibers (PCNFs). The support structure-dependent performance-degradation characteristic is analyzed in a single cell by performing an electrochemical analysis of the kinetic resistance, ohmic resistance, and diffusion resistance. In addition, the characterization of the catalyst layer structure before and after the deterioration is performed to understand the deactivation mechanism. This study is expected to provide a design strategy from a structural perspective of carbon support for the development of highly durable MEAs.
Keywords: Carbon corrosion; Deactivation mechanism; Electrochemical analysis; Membrane electrode assemblies; One dimensional (1D) structures; Performance degradation; Platelet carbon nanofibers; Polymer electrolyte fuel cells; Carbon corrosion; Carbon nanofiber; Durability; Membrane electrode assembly; Polymer electrolyte fuel cell